The relationship between the development of response inhibition and intelligence in preschool children - Lee, Hon Wah; Lo, Yu-Hui; Li, Kuan-Hui; Sung, Wen-Shin; Juan, Chi-Hung (Frontiers in Psychology, 2015)
Building on the theoretical framework that intellectual behavior relies on one’s ability to process both task-relevant and task-irrelevant information, this study aimed to empirically investigate the association of response inhibition with intelligence in preschool children’s development. In a sample of 152 typically developing children aged between 3.6 and 6.6 years, we found evidence that suggests that inhibitory control is linked to age-related differences in intelligence. Stop-signal inhibition improved at a rate similar to the age-related changes in Verbal IQ. Components of variance analyses revealed that stop-signal reaction time predicted a larger proportion of the age-related variance in children’s verbal intelligence than non-age-related variance. Results are discussed with respect to possible explanations for this intriguing relationship between response inhibition and the verbal aspects of intelligence.